Analysis of Legal Protection of Labor in the Implementation of Layoff - Nely Anggraeni; Indra Koswara; Yopie Gunawan (IHSA Institute, 2022)
Employment relationships can lead to various consequences, one of which is layoffs. The impact is very complex. Therefore Who must regulate the mechanisms and procedures in such a way. The goal is that workers/laborers still get proper protection and obtain their normative rights by applicable legal provisions. Because the workforce has a significant role and position as actors in the national development goals, namely creating a prosperous, just, prosperous society that is evenly distributed both materially and spiritually based on Pancasila and the 1945 Constitution of the Republic of Indonesia. Legal protection for workers is based on the provisions of Article 27 (1), paragraph (2), Article 28 D paragraph (1), paragraph (2), the 1945 Constitution. If a layoff occurs, the workers/laborers who have been laid off must receive compensation in the form of severance pay, service fees, and Replacement of rights following the provisions of Law no. 13 of 2003 and Law No. 2 of 2004 In resolving layoffs, judges must be able to provide legal certainty and protection for workers. The judge's consideration is the soul and essence of the decision.